Effect of siblings and type of delivery on the development of motor skills in the first 48 months of life - Rebelo, Miguel (2020)
This study aimed to verify whether the presence of siblings and the type of delivery had an influence on the motor skills development of children in the first 48 months of life. We developed a quantitative study with a sample of 405 children of both genders, divided according to the studied variables: children with siblings, children without siblings, children born via eutocic delivery, and children born via dystocic delivery. The instrument used in the study was the Peabody Developmental Motor Scales-2. Overall, the results indicated that children who had siblings had, on average, better outcomes regarding all motor skills (global and fine). Furthermore, those born via eutocic delivery, on average, had better outcomes regarding all motor skills (global and fine) when compared to children born via dystocic delivery. Thus, the presence of siblings in the family context and the type of delivery positively influenced motor development, especially after 24 months of age, showing that the presence of siblings providing cooperative activities through play and challenges improved cognitive, social, emotional, and physical development. Furthermore, a eutocic delivery, in addition to providing a better recovery from labor and the immediate a ective bond between mother and child, also led to better results in terms of global and fine motor skills.